Desamparo psíquico na contemporaneidade - Oliveira, Adriana Aparecida Almeida de [UNESP] (2014)
This article has as a purpose to make a theoretical reflection on the experience of helplessness in the recent days. It starts from the Freud’s concept of helplessness, and compares it with analyses and reflections from contemporary authors on models of subjectivation which have risen at the present time. In the first experiences of life helplessness comes out as a result of an incompleteness of the organism, its need to perform exchanges with the world, and the extreme dependency on help from others. On the one hand, the contemporary culture highlights the individualism, which indicates good possibilities for granting desires. On the other hand, it makes bonds and relationships ephemeral and fragile. At the absence of a solid, safe and stable continent for affective and emotional experiences a feeling of helplessness appears. It activates primary defense mechanisms, contributing to the intensification of regressive forms of subjectivation and the decline of the symbolic sphere.